Molodhen Tradition as a Harmonization of Socio-Cultural Values - Windisari, Yuliana; Farid, Mohtazul; Biroli, Alfan; Wardhana, Indra Jaya Kusuma; Retnosari, Putri (International Journal of Linguasphere, 2025)
Molodhen (Maulid Nabi Muhammad SAW) tradition is one of the religious traditions related to socio-cultural values, because the existence of the tradition is related to other factors outside of religious values, socio-cultural values in the tradition of celebrating the prophet’s maulid are related to solidarity in the life of the people of Madura. The people of Madura who have been known as religious, traditional and have a high work ethic still uphold the socio-cultural values of the community, especially traditions that are traditional, distinctive and local wisdom. The tradition of celebrating the prophet’s maulid is a form of harmonization between the socio-cultural values of the community and religious aspects. Based on the results of observations, it is known that the tradition of the Prophet’s Maulid in Bangkalan Regency, Madura shows that the community participates in its celebration through activities such as tasyakuran, celebration through the tradition of hadrah music and other traditions such as recitation, inviting scholars or religious leaders to be given lectures related to the exemplary values of the Prophet Muhammad SAW. The tradition of the Prophet’s Maulid Celebration in Bangkalan Regency, Madura provides a conclusion that there are still people who have concern for local traditions, especially in the context of passing on traditions to the next generation, especially in families in the Bangkalan Regency area, the Prophet’s Maulid Celebration Tradition is also a symbol that religious values are still a sacred thing in the socio-cultural life of the Madurese ethnic community